IDENTITEETISTÄ INFORMAATIOLUKUTAITOON: tavoitteena itsenäinen ja yhteisöllinen oppija - Ropo, Eero; Sormunen, Eero; Heinström, Jannica (Tampere University Press, 2015)
Developing independence as a learner is necessary for becoming a lifelong learner in an increasingly changing world. However, an individual without a community and socially shared learning processes is not an ideal for learning the skills for cooperation, creativity, or solving common problems. This book introduces the readers the perspective of identity development to learning processes, and particularly the questions of learning information literacy. The revised national school curriculum 2014 in Finland (implemented from Fall term 2016) emphasizes developing the students' metaskills for learning. These metaskills can be described as aptitudes and skills for independent knowledge acquisition, problem-solving and creative thinking. This will act as a framework for the book. The contents includes discussion on the concepts of identity and information literacy, and their central role in becoming an independent learner willing to share and learn from others. The book also discusses enhancing the identity development processes and reaching the skilled levels of information literacy. The book is intended for teachers interested in developing pedagogical practices. It will also help pedagogically thinking information professional to develop their instruction and information training. The ideas and frameworks introduced in the book will also be useful for students in education, informatics and other areas which explore issues of identity development and information literacy.